The role of opioid transmission in music‐induced pleasure - Mas‐Herrero, Ernest; Ferreri, Laura; Cardona, Gemma; Zatorre, Robert J.; Pla‐Juncà, Francesc; Antonijoan, Rosa María; Riba, Jordi; Valle, Marta; Rodriguez‐Fornells, Antoni (Annals of the New York Academy of Sciences, 2023)
Studies conducted in rodents indicate a crucial role of the opioid circuit in mediating objective hedonic reactions to primary rewards. However, it remains unclear whether opioid transmission is also essential to experience pleasure with more rewards, such as music. We addressed this question using a double‐blind within‐subject pharmacological design in which opioid levels were up‐ and downregulated by administering an opioid agonist (oxycodone) and antagonist (naltrexone), respectively, before healthy participants (n = 21) listened to music. Participants also performed a monetary incentive delay (MID) task to control for the effectiveness of the treatment and the specificity of the effects. Our results revealed that the pharmacological intervention did not modulate subjective reports of pleasure, nor the occurrence of chills. On the contrary, psychophysiological (objective) measures of emotional arousal, such as skin conductance responses (SCRs), were bidirectionally modulated in both the music and MID tasks. This modulation specifically occurred during reward consumption, with greater pleasure‐related SCR following oxycodone than naltrexone. These findings indicate that opioid transmission does not modulate subjective evaluations but rather affects objective reward‐related psychophysiological responses. These findings raise new caveats about the role of the opioidergic system in the modulation of pleasure for more or cognitive forms of rewarding experiences, such as music. It remains unclear whether opioid transmission is essential to experience pleasure with rewards, such as music. We manipulated the opioid system pharmacologically by administering an opioid agonist (oxycodone) and antagonist (naltrexone) prior to a music listening or monetary‐incentive delay (MID) task. Pharmacological manipulation modulated reward‐related psychophysiological measures in the music and MID tasks but not subjective ratings, indicating that opioid transmission affects objective, reward‐related psychophysiological responses.